Canvas Model Business as an Innovation of Teaching Factory Learning in the Fashion Department of 27 Public Vocational High School, Jakarta - Wahjusaputri, Sintha; Fitriani, Somariah; Syarif, Suryadi (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
This research was an attempt to design and enhance the Canvas Model Business of nine blocks in one canvas within teaching factory based learning innovation at the Fashion Department of 27 Public Vocational High School, Jakarta. The research method used qualitative and quantitative methods. The qualitative method, data collection was conducted within a SWOT analysis. This research was conducted in 27 Public Vocational High School, Jakarta, with the respondents were 82 students. The quantitative method with in the matrices of Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE). The result of this research that implementation of the Canvas Model Business: (1) Customer Relationships in strategy 1 was valued of 0.34, was